2016
DOI: 10.1111/jipb.12444
|View full text |Cite
|
Sign up to set email alerts
|

Putative zeatin O‐glucosyltransferase OscZOG1 regulates root and shoot development and formation of agronomic traits in rice

Abstract: As a ubiquitous reaction, glucosylation controls the bioactivity of cytokinins in plant growth and development. Here we show that genetic manipulation of zeatin-O-glucosylation regulates the formation of important agronomic traits in rice by manipulating the expression of OscZOG1 gene, encoding a putative zeatin O-glucosyltransferase. We found that OscZOG1 was preferentially expressed in shoot and root meristematic tissues and nascent organs. The growth of lateral roots was stimulated in the overexpression lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 58 publications
(111 reference statements)
2
29
0
Order By: Relevance
“…Strain YC0136 attenuated the ability of zeatin conversion in tobacco by inhibiting the expression of cis-zeatin O-glucosyltransferase. This reduced the degradation of zeatin, allowing zeatin to play a role as a cytokinin (Kudo et al, 2012;Shang et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Strain YC0136 attenuated the ability of zeatin conversion in tobacco by inhibiting the expression of cis-zeatin O-glucosyltransferase. This reduced the degradation of zeatin, allowing zeatin to play a role as a cytokinin (Kudo et al, 2012;Shang et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…For examples, exogenous CK could increase rice yield potential by enhancing grain filling and bearing large panicles (Panda et al, 2018). Downregulation of OsCKX2 and OscZOG1 resulted in elevated CKs, and thereby improved yield-related traits including tiller numbers, panicle branches, and grain number per panicle in rice (Ashikari et al, 2005; Shang et al, 2016). Similarly, GA20ox1 affected grain number and yield by rebalancing activities of CKs and GAs in rice (Wu et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, zeatin O-glucosyltransferase (Unigene0016372), a protein related to zeatin biosynthesis, was obviously increased in sugar beet exposed to salt. It was observed that zeatin O-glucosyltransferase OsZOG1 regulates root and shoot development and formation of agronomic traits in rice [58]. Overexpression of a zeatin O-glucosyltransferase gene significantly enhanced the accumulation of both CK and auxin in roots and lower leaves of transgenic tobacco plants when subjected to water deficit [59].…”
Section: Discussionmentioning
confidence: 99%